Komsumsi Makanan Sehat Untuk Meningkatkan Sikap Dan Pengetahuan Anak Usia Sekolah Melalui Pendidikan Kesehatan - Iriani, Restu; Abdullah, Abdullah; Saraswati, Dika; Nawangwulan, Kurniati; Yusfik, Yusnita; Sallo, Andi Kamal M.; Jamin, Nunung Suryana; Rahim, Abdul (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Children's eating patterns for each age are not the same. The energy needs of the 10-12 year age group are relatively greater than the 7-9 year age group, because growth occurs faster, especially the increase in height. The purpose of Community Service is to improve the attitudes and knowledge of school-age children through health education. The method of implementing the activity is carried out by increasing student knowledge, so health education is carried out by showing videos through projectors, books and games at SD Negeri Kota Depok, West Java. The calculation results obtained an average student food knowledge score of 13.78 so that the average student food knowledge score is in the sufficient category. The conclusion is that the knowledge about food of grade 5 students at SD Negeri Kota Depok shows that the good category is 19 respondents (37.26%), the sufficient category is 30 respondents (58.82%), and the lacking category is 2 respondents (3.92%).